Genes and cardiovascular function - Oésítâadal, Bohuslav; Nagano, Makoto 1928-; Dhalla, Naranjan S. (Springer, 2011)
Rapid advances in molecular medicine have led to pronounced new developments in experimental and clinical cardiology. In the embrace of modern molecular biology and bridging the gap between the clinical and the genomic, cardiovascular medicine has seen major strides in the understanding of the molecular mechanisms that drive disease progression. The ability to rapidly identify candidate human genes for cardiovascular diseases lends itself to the development of diverse strategies for disease treatment and management. The wide variety of gene expressions proffers excellent targets for novel there.